A novel bio-based flame retardant for polypropylene from phytic acid. (March 2019) - Gao, Yu-Yang; Deng, Cong; Du, Yuan-Yuan; Huang, Sheng-Chao; Wang, Yu-Zhong
Abstract: Phytic acid mainly exists in seeds, roots and stems of plants, which has a potential value in flame-retarding polymers due to the high content of phosphorus. In this work, a novel bio-based phytic acid salt PHYPI was prepared through a salt formation reaction between phytic acid and piperazine. The structure of the bio-based PHYPI was verified using 1 H NMR spectrascoppy. When PHYPI was used to fabricate flame-retardant polypropylene (PP), it showed high efficiency in combustion tests. The limiting oxygen index (LOI) value for PP containing 18.0 wt% PHYPI is 25.0%, showing a 38.9% increase compared to 18.0% for PP containing no additive. Moreover, it passed the UL-94 V-0 rating in the vertical burning test, superior to the no rating for pure PP. Obviously, the flame-retarding efficiency of PHYPI is higher than that of typical traditional intumescent flame retardant containing ammonium polyphosphate or pentaerythritol. Cone calorimeter test revealed that the heat release and smoke production of PP were efficiently restrained by the presence of PHYPI. The peak of heat release rate (PHRR), total heat release (THR), and the peak of smoke release rate (PSPR) for PP containing 20 wt% PHYPI were decreased by 65.6%, 13.5%, and 32.8%, respectively, compared to the same values for PP alone. Fourier transform infrared spectroscopy (FTIR) was used to investigate the changes which accompanied the thermal degradation of the polymer containing PHYPI. Changes in the infrared spectra for the polymer undergoing degradation indicate that structures containing C=C and P-N-C were formed as a consequence of the presence of PHYPI. These transformations enhanced char formation to provide condensed phase protective action. At the same time, non-combustion volatile gases such as water and carbon dioxide may be released to dilute the fuel load in the gas phase. All evidences illustrate that PHYPI is an effective flame retardant for PP. Highlights: A novel bio-based flame retardant named PHYPI from phytic acid. High flame-retarding efficiency of PHYPI for polypropylene. Flame-retardant mechanism of polypropylene/PHYPI.